Effect of food source on the chemical composition of Californian red worm (Eisenia foetida) vermicompost - Riascos, A. R.; Crespo-López, G.; Guerrero, E. M.; Medina, Yolaine (Cuban Journal of Agricultural Science, 2023)
In an area of the Amazon plain, the effect of the food source on the chemical composition of the Californian red worm (Eisenia foetida) vermicompost was evaluated. The research was carried out at "El mochilo” farm, from Centro Agroforestal y Acuícola “Arapaima”. An analysis of variance was performed, according to a random block design. Three treatments and three replications were established: T1) 100 % fruit and vegetable wastes, T2) 100 % chicken manure wastes and T3) mixture of 30 % bovine manure, 35 % chicken manure and 35 % fruit and vegetable wastes. The variables electrical conductivity, pH, organic matter content, nitrogen, phosphorus, potassium and C/N ratio were measured. Analysis of variance was performed Duncan (1955). The treatments with the highest amount of fruit and vegetable wastes (T1 and T3) obtained higher potassium contents, with values of 1.23 % and 1.20 %, respectively, compared to 100 % chicken manure, which obtained higher phosphorus content, pH value of 7.23 with better vermicomposting stability. The research showed that, according to their chemical composition, the different sources for the elaboration of vermicompost constitute a viable option to obtain a quality product. A higher content of fruits and vegetables achieved more potassium in the final product. On the contrary, higher phosphorus and organic matter contents were recorded from a source that contained chicken manure. Key words: fertilizer, organic matter, potassium